Evaluasi Kinerja Simpang Lima di Kabupaten Gowa - Yusuf, Yusriyyah Mardhiyyah; Rumata, Nini Apriani; M. Nurhidayat (LOSARI : Jurnal Arsitektur Kota dan Pemukiman, 2025)
This intersection is a commercial area with many shops, restaurants, and offices, and is the main access to the Twin Bridges of Gowa, which is the only access road between districts/cities. Congestion is caused by high traffic volumes at certain time periods, road user behavior and heavy load vehicles often crossing the intersection. This study is to evaluate the performance of the intersection using the Calculation method with the equation of the Indonesian Road Capacity Manual (MKJI) 1997 to obtain performance evaluation results and efforts to overcome congestion problems at the intersection. The results show that the high volume of traffic in the morning and evening with the available road capacity cannot meet the volume of vehicles passing through the intersection. Thus the degree of saturation shows a very saturated level with traffic density, congestion and poor traffic performance. The level of service is rated F (very poor) with a delay value (D) ≥60.0. Indicating extreme congestion conditions, drivers will have difficulty navigating through the intersection with severely constrained travel times. Thus, several measures are needed to address the problem, such as adjustment and optimization of traffic signal duration, traffic regulation and management, analysis and long-term planning.